المقايضة بين متطلبات التغير الهيكلي في الإقتصاد العراقي وتوفير الحاجات الأساسية للمجتمع للمدة 2003 - 2013 - المعموري، محمد علي موسى Almaamouri, Mohammed Ali Mousa (الجامعة المستنصرية - مركز المستنصرية للدراسات العربية والدولية, 2015)
إن الدور الذي تلعبه النفقات العامة يكتسب أهمية بالغة في الاقتصاد الوطني، وإذا كان الهدف من الإنفاق العام هو إشباع الحاجات العامة فإلى أي حد يجوز للدولة أن تذهب في إشباع هذه الحاجات، وما هو الحد الذي ينبغي لها أن تقف عنده مقابل المتطلبات الملحة من الإنفاق لمقابلة التدهور الحاصل في بنية الاقتصاد القومي وتخلف قطاعاته المختلفة. علما أن التشوه الهيكلي في الاقتصاد العراقي، ونتيجة للضغوطات السياسية والاجتماعية، وصل إلى المستوي الذي يصعب تشخيصه فضلا عن علاجه، بسبب إعطاء الأولوية للحاجات العاجلة، وعدم الاهتمام بتنمية الاقتصاد وتطوره. ويهدف هذا البحث إلى تحديد السياسة المالية المثلي لتحقيق الأهداف الاقتصادية والاجتماعية العامة، وبيان الحد الأمثل للإنفاق العام وفق الاحتياجات الضرورية لتطوير الاقتصاد وتحقيق متطلبات المجتمع وصولا إلى تحقيق التوازن الاقتصادي العام. باعتبار أن المقايضة بين البدائل في تخصيص الموارد تقوم على اعتماد الأولوية بين الأهداف، كما أن متطلبات التنمية الاجتماعية واستدامتها لا يمكن إن تتحقق إلا من خلال التغير الهيكلي في الاقتصاد.
Teh role of public expenditures is of great importance in teh national economy. If teh goal of public spending is to satisfy teh public needs to what a State may has to go to satisfy these needs, and what is teh extent that they should end at trading teh urgent requirements of expenditures against deterioration in teh structure of teh national economy and teh failure of teh various sectors. Note that teh structural distortion in teh Iraqi economy, and as a result of political and social pressures, arrived at a level that is difficult to diagnose as well as treat, coz of teh priority given to teh urgent needs and teh lack of attention to developing teh economy and it's development. This research aims to determine teh optimal financial policy to achieve teh general economic and social goals, and optimization of public spending in accordance wif teh requirements necessary to develop teh economy and to achieve teh requirements of society and thus achieving teh general economic balance. Considering that teh trade-off between alternatives in teh allocation of resources is based on teh adoption of goals priority, in addition to that teh requirements of social development and sustainability can not be achieved unless there is a structural change in teh economy.
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- النمو الإقتصادي -- المقايضة -- القوانين والتشريعات -- العراق -- المجتمع العراقي